Evaluation of Adult Level of Knowledge, Awareness of Malocclusion and Barriers to Uptake Orthodontic Care Among Patients - Arora, Swati; Buvariya, Shreya; Mohankumar, Karthiga; Chhina, Jageer; Hawaii, Ibrahim; Rodagi, Akshata (International Journal of Psychosocial Rehabilitation, 2020)
Background: Malocclusion is the most common dental health problem encountered worldwide. It is defined as a discrepancy in the position of the maxillary and mandibular arches with a characterized anomaly in the position of the tooth, form, and number. The present study was conducted to assess adult levels of knowledge and awareness of malocclusion and barriers to uptake of orthodontic care among patients. Materials & Methods: The present study comprised 470 subjects of both genders in Indore, Madhya Pradesh. A questionnaire was prepared that comprised questions pertaining to oral and dental habits, parafunctional habits, etc., and was recorded. Results: Out of 470 subjects, 240 were males and 230 were females. 65% replied that gingivitis (gum problems) may result from malocclusion, 20% replied no, and 15% replied don’t know. 75% thought that it is difficult to brush teeth with malocclusion, 15% replied no, and 10% replied, Don’t know. Barriers to orthodontic care were cost in 54%, repeated dental visits in 20%, long-term treatment in 10%, requirement of good oral hygiene maintenance in 6% of cases, accessibility in 7%, and postoperative pain in 5%. Conclusion: Authors found that subjects had knowledge and awareness regarding orthodontic care. Major barriers to orthodontic treatment were found to be cost, repeated dental visits, long-term treatment, the requirement of good oral hygiene maintenance, accessibility, and postoperative pain.